Bone fragility in Turner syndrome: Fracture prevalence and risk factors determined by a national patient survey. (8th May 2018) - Wasserman, Halley; Backeljauw, Philippe F.; Khoury, Jane C.; Kalkwarf, Heidi J.; Gordon, Catherine M.
Summary: Objective: Osteoporosis is considered a comorbidity of adult women with Turner syndrome (TS). Limited data are available on fracture prevalence in girls and women with this diagnosis. We aimed to determine the prevalence of fractures in individuals with TS in the United States and identify risk factors for fracture. Design: Girls and women with TS were invited to participate in an anonymous, self‐report, national survey from November 2016 to March 2017. Non‐TS controls were obtained through direct contacts of TS participants. Results: During childhood (0‐12 years), adolescence (13‐25 years) and young adulthood (26‐45 years), there was no difference between TS and controls in fracture prevalence. Girls and women with TS were more likely to report upper extremity fractures, whereas controls were more likely to report phalangeal fractures. Older women (>45 years) with TS were more likely to fracture than non‐TS controls ( P  = .01). Balance problems were more common in individuals with TS than controls (26.5% vs 14.8%, P  = .0006). In TS, those reporting balance problems were 54% more likely to have a prior fracture than those without balance problems (OR=1.54, 95% CI 1.03, 2.30), even after controlling for age. There was no significant association between balance problems and fractures among controls. Conclusions: In a nationwide survey, there was no difference in fracture prevalence in younger women with TS compared with controls. However, the location of fractures differed. After controlling for age, impaired balance was associated with an increased fracture risk in TS and may be an underrecognized risk factor for fracture in this population.